2001
DOI: 10.1007/s00223-001-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine on Bone Mass, Turnover, and Strength in Adult Female Rats

Abstract: This study investigated the effects of nicotine, the chemical responsible for tobacco addiction, on bone and on serum mineral and calcitropic hormone levels in adult, female rats to help resolve a current controversy regarding the impact of nicotine on bone health. Seven-month-old rats received either saline (n = 12), low-dose nicotine (4.5 mg/kg/day, n = 2), or high-dose nicotine (6.0 mg/kg/day, n = 12) administered subcutaneously via osmotic minipumps for 3 months. Blood, femora, tibiae, and lumbar vertebrae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 26 publications
3
31
1
2
Order By: Relevance
“…Our data show that CSM induces osteoblast damage alongside with an increase in ROS formation that was already seen after a 15 min treatment with CSM. This is supported by several publications, suggesting a positive correlation between increased oxidative stress and cell death in osteoblasts, influencing fracture healing, bone regeneration, and bone mineral density [3,4,6,7,13,44,45]. This emphasizes the need for new treatment strategies to reduce oxidative stress in patients, e.g., smokers that are reported to have strongly elevated oxidative stress levels.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our data show that CSM induces osteoblast damage alongside with an increase in ROS formation that was already seen after a 15 min treatment with CSM. This is supported by several publications, suggesting a positive correlation between increased oxidative stress and cell death in osteoblasts, influencing fracture healing, bone regeneration, and bone mineral density [3,4,6,7,13,44,45]. This emphasizes the need for new treatment strategies to reduce oxidative stress in patients, e.g., smokers that are reported to have strongly elevated oxidative stress levels.…”
Section: Discussionmentioning
confidence: 52%
“…This is contradictory to our findings that clearly show a positive correlation between increasing ROS levels and cell damage in primary human osteoblasts, suggesting bone loss in vivo. This is supported by several publications, investigating the effect of cigarette smoke on bone mineral density and fracture healing in rodents [3,4,6,7,13,44,45] that clearly show a negative effect of cigarette smoking on bone. Our results suggest a direct toxic effect of cigarette smoke on the bone-forming osteoblasts.…”
Section: Discussionmentioning
confidence: 55%
“…17,18 Nicotine has been shown to increase the level of mammalian parathyroid hormone. 19 It is proposed that the greater the tobacco consumption and duration of the habit, the greater the signifi cance of tobacco as a co-risk factor for BONJ.…”
Section: Smokingmentioning
confidence: 99%
“…The chemical effect of the nicotine inhaled, added to tobacco, in the indexes of mineral serumal and calcium hormones in adult rats was investigated by Iwaniec et al 12 and Syversen et al 13 in order to elucidate controversy, approaching the impact of nicotine in bone integrity. Such authors observed that the treatment with nicotine did not have effect on the medular bone or tibia cortical turnover or on the content and mineral bone density.…”
Section: Discussionmentioning
confidence: 99%